Constantine Roman emperor, Christian victor - Stephenson, Paul (Overlook Press, 2010)
In 312 A.D., Constantine-one of four Roman emperors ruling a divided empire-marched on Rome to establish his control. On the eve of the battle, a cross appeared to him in the sky with an exhortation, "By this sign conquer." Inscribing the cross on the shields of his soldiers, Constantine drove his rivals into the Tiber and claimed the imperial capital for himself. Under Constantine, Christianity emerged from the shadows, its adherents no longer persecuted. Constantine united the western and eastern halves of the Roman Empire. He founded a new capital city, Constantinople. Thereafter the Christian Roman Empire endured in the East, while Rome itself fell to the barbarian hordes. Paul Stephenson offers a nuanced and deeply satisfying account of a man whose cultural and spiritual renewal of the Roman Empire gave birth to the idea of a unified Christian Europe underpinned by a commitment to religious tolerance.